2011
DOI: 10.1007/s11243-011-9523-x
|View full text |Cite
|
Sign up to set email alerts
|

Aquachlororuthenium(III) catalysis in the oxidation of substituted 4-oxo-4-arylbutanoic acids by bromate in acid medium: a kinetic and mechanistic study and validity of linear free-energy relationships

Abstract: Ru(III) acts an efficient catalyst in the oxidation of substituted 4-oxo-4-arylbutanoic acids (4-oxo acids) by bromate in sulfuric acid medium, giving the corresponding benzoic acids in quantitative yields. The reaction shows first-order dependence in both [bromate] and [H 2 SO 4 ], and a non-linear dependence on both [oxo acid] and [catalyst]. Changing solvent from H 2 O to D 2 O increases the rate. The rate is not affected by ionic strength but decreases with increase in dielectric constant of the medium. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It can be observed that the deviations of the enthalpy increased linearly with those of the entropy, the slope (T) being dimensionally a temperature. This and other statistical parameters were systematically analyzed for 10 homologous reaction series searched in the chemical literature [59][60][61][62][63][64]. Since it has been demonstrated [35][36][37] that the random errors of the activation enthalpy are directly proportional to those of the entropy, according to the equation:…”
Section: Effect Of Experimental Random Errors: a Critical Appreciationmentioning
confidence: 99%
“…It can be observed that the deviations of the enthalpy increased linearly with those of the entropy, the slope (T) being dimensionally a temperature. This and other statistical parameters were systematically analyzed for 10 homologous reaction series searched in the chemical literature [59][60][61][62][63][64]. Since it has been demonstrated [35][36][37] that the random errors of the activation enthalpy are directly proportional to those of the entropy, according to the equation:…”
Section: Effect Of Experimental Random Errors: a Critical Appreciationmentioning
confidence: 99%